Physicochemical properties and frauds in the samples of raw cow milk produced in Qazvin, Iran - Razzagh Mahmoudi; Reza Norian (Gonabad University of Medical Sciences, 2015)
Adding materials to reduce the microbial load and cover to deficit in milk is a health threat and has always provided consumer concern.112 raw cow milk samples were randomly collected from dairy industrial centers of Qazvin province during warm and cold seasons in 2012, physicochemical and added adulteration were investigated. Based on the results of chemical tests, the mean values of the lactose, density and solid non fat (SNF) milk samples examined in most cases in most cases was within the average range. However, the mean value amount of fat (2.48) and protein (2.32) samples was significantly lower than average range (P<0.05).The tests were carried out to determine the adulteration of milk samples indicate that the added water (16.07%), sodium hypochlorite (0.89%) and hydrogen peroxide (1.78%) were positive and In the other test results were negative. In this regard, the milk samples containing added water in the hot season were significantly higher than compared to cold season (P<0.05). Therefore, quality control of this product with high per capita consumption, which have a special place in the human diet, especially for children is necessary for physiochemical properties and added adulteration.